CORRUPTION AND UNDERGROUND ECONOMY: ESTIMATING ITS SIZE IN PAKISTAN - Fatima Javed; Khawaja Asif Mehmood; Muhammad Zahir Faridi; Roeela Kausar; Muhammad Aurmaghan, (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
The study aims to evaluate the influence of corruption on the size of underground economy of Pakistan against tax revenue, political stability, voice and accountability, gross domestic product, inflation, and corruption. To assess the influence of corruption on the magnitude of the underground economy, annual time series data from 1972 to 2021 is used. For the regression analyses, Auto Regressive Distributed Lag (ARDL) framework is utilized. The explained variable in the study is the ratio of currency in circulation and money supply. The empirical findings reveal significant impact of explanatory variables. Appropriate tax adjustments, promotion of education and awareness, and price stability are the policy recommendation to combat the issue of underground economy.